The rise and fall of the American Jewish PhD - Barry R. Chiswick (Institute for the Study of Labor (IZA), 2008)
This paper is concerned with trends over the post-WWII period in the employment of American Jews as College and University teachers and in their receipt of the PhD. The empirical analysis is for PhD production from 1950 to 2004 and Jews are identified by the Distinctive Jewish Name (DJN) technique. Descriptive statistics and multiple regression analyses are reported. Central roles are played in the regression analysis by variables for military conscription, the Korean and Vietnam Wars, and US government funding for research and development. Among the DJNs, the simple data show that male PhD graduates increased in number in the post-war period up to early 1970s, and declined thereafter. Among DJN women, however, annual PhD production increased throughout the period. The ratio of DJN to all PhDs declined throughout the period for both men and women. Other variables the same, male DJN PhD production increased to about 1967 and then declined, while for DJN females it increased throughout the period. The ratio of DJN to all PhDs started to decline among men in the 1950s and continued thereafter, while among women the DJN share increased until about 1979, and then declined. These data are consisted with the hypothesis that discrimination against Jews in salaried professional occupations declined in the post-WWII period earlier in College and University teaching than in other sectors of the economy that do not require a PhD degree for employment.
Keywords: I21; 330; American Jews; education; discrimination; gender; Arbeitsmarktdiskriminierung; Juden; Bildungsverhalten; Geschichte; Akademische Berufe; Geschlecht; USA